2018
DOI: 10.1155/2018/6428492
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Pleomorphic Xanthoastrocytoma Presenting with Musical Hallucination

Abstract: Musical hallucinations are a relatively rare form of auditory hallucination characterized by hearing of music in the absence of any external stimuli. This phenomenon has been linked to both psychiatric and structural lesions. We present the case of a previously healthy young male whose presentation with musical hallucinations led to the diagnosis of a rare tumour, anaplastic pleomorphic xanthoastrocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Although cases are infrequent in the young age group, such neoplasm could be diagnosed in a wide range of ages and are responsible for less than one percent of all brain tumors [ 9 ]. Furthermore, seizures in general are the most common presentation, and even musical hallucination was reported [ 11 ]. Concerning the anatomical distribution, the frontal lobe is affected in the third position of supratentorial sites, and the rarest cases were described as infratentorial [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cases are infrequent in the young age group, such neoplasm could be diagnosed in a wide range of ages and are responsible for less than one percent of all brain tumors [ 9 ]. Furthermore, seizures in general are the most common presentation, and even musical hallucination was reported [ 11 ]. Concerning the anatomical distribution, the frontal lobe is affected in the third position of supratentorial sites, and the rarest cases were described as infratentorial [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors concluded that both radiotherapy and chemotherapy are not recommended for PXA [ 6 ]. Conversely, anaplastic PXA deserves a complementary therapy [ 7 , 11 ]. However, according to the latest WHO classification of 2016 [ 15 ], PXA and anaplastic PXA were considered as distinct entities.…”
Section: Discussionmentioning
confidence: 99%
“…One case report identified an uncommon but increasingly recognized anti-IgLON5 disease accompanied by MHs [13], which demonstrates the diverse and ever-changing clinical phenotypes observed in autoimmune central nervous system diseases. Chronic pain, electrical stimulation of the anterior cingulate cortex for refractory chronic pain, anaplastic pleomorphic xanthoastrocytoma, hybrid cochlear implantation, insular glioma resection, left temporal lobectomy, abdominal pain, and electroconvulsive therapy were the other causes of MHs in the NOC group [14,24,28,36,58,61,65,67].…”
Section: Not Otherwise Classifiablementioning
confidence: 97%